Congenital Cytomegalovirus Infection in High-Risk Canadian Infants: Report of a Pilot Screening Study - Wendy Vaudry; Rhonda J Rosychuk; Bonita E Lee; Po Yin Cheung; XL Pang; Jutta K Preiksaitis (Canadian Journal of Infectious Diseases and Medical Microbiology, 2010)
OBJECTIVES: Congenital cytomegalovirus (cCMV) is the most common congenital infection; however, the epidemiology in Canada has not been recently examined. The present prospective study pilots tools for a population-based study of cCMV infection in Canada by determining the maternal seroprevalence and risk factors, the clinical characteristics and the incidence of cCMV using a variety of diagnostic tests in a cohort of high-risk infants in northern Alberta.